EMERGENCY INCIDENTS AND POSSIBILITIES OF LIQUIDATION OF THEIR CONSEQUENCES IN THE THERMS OF INLAND NAVIGATION (Perner's Contacts, 2015)
Paper describes emergency incidents created in inland navigation and possible steps of liquidation of their consequences. It informs about technical recommendations for the transport of dangerous goods..
Keywords: emergency incident, waterway, oil spill